Brand logo design : how does brand name and logo naturalness influence consumers’ cognitive and affective responses? - Costa, Mariana Monteiro Rolo Trindade (2022)
The name and logo are the most important brand identity signs, as they can help identify a product or brand, provide differentiation from competition and influence consumers’ choices. As such, firms spend extensive amounts of resources in selecting an appropriate name and logo. Therefore, proper selection guidelines are critical in helping firms make decisions that will help them achieve their strategic objectives. This study explores how brand name and logo design influence consumer’s cognitive and affective responses. In particular, this research aims to determine if the level of naturalness of brand names and logos, has a significant effect on brand recall, recognition and associations and on affect. First, a comprehensive literature review is presented, where the variables investigated in this research are analysed. Following that, a research model and research hypotheses were developed. In order to test the hypotheses, a quantitative research was conducted through an online survey, among the Portuguese population. This study used, as stimuli, a sample of fictitious and manipulated logos, ranging from very abstract to very natural. Respondents were randomly divided into nine experimental groups, with a total sample of 275 respondents. The results suggest that naturalness in name and logos significantly increases recall, recognition, associations and affect, and that, within natural names and logos, organic ones are the ones that obtain the best performance, as organicity significantly improves recall and affective responses.